2022
DOI: 10.3390/ani12020172
|View full text |Cite
|
Sign up to set email alerts
|

Plumage Response of Young Turkeys to Diets with Increased Methionine to Lysine Ratios at Three Dietary Arginine Levels

Abstract: A 2 × 3 factorial experiment was conducted to evaluate the effects of two dietary methionine levels (Met; 30% and 45% of Lys content) and three arginine levels (Arg; 90%, 100%, and 110% of Lys content) on plumage development in 4- and 16-week-old female turkeys. One-day-old turkey poults were assigned to six groups (eight replicate pens per group and 18 birds per pen) and fed experimental diets containing 1.6%, 1.5%, 1.3%, and 1.0% of Lys in four successive four-week periods. After weeks 4 and 16 of feeding, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The higher dietary Met level (45% vs. 30% of Lys content) increased plasma albumin concentration and stimulated the antioxidant defense system of 16-week-old turkeys . In turn, Mróz et al (2022) demonstrated that an increased supply of Met to 45% of Lys content accelerated the development of feathers, compared with birds fed a diet with a lower Met level. The lowest Arg level (90% of Lys content) undesirably increased the concentration of the proinflammatory cytokine IL-6, decreased globulin con-centration in the blood plasma, and decreased the dressing yield of turkeys .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The higher dietary Met level (45% vs. 30% of Lys content) increased plasma albumin concentration and stimulated the antioxidant defense system of 16-week-old turkeys . In turn, Mróz et al (2022) demonstrated that an increased supply of Met to 45% of Lys content accelerated the development of feathers, compared with birds fed a diet with a lower Met level. The lowest Arg level (90% of Lys content) undesirably increased the concentration of the proinflammatory cytokine IL-6, decreased globulin con-centration in the blood plasma, and decreased the dressing yield of turkeys .…”
Section: Discussionmentioning
confidence: 95%
“…of dietary Met (45 vs. 30% of Lys content) increased the body weight gain (bwg) and final body weight (bw) of 16-week-old turkeys, whereas Arg levels (100% and 110 vs. 90% of Lys content) had a limited influence on their growth performance . It was also demonstrated that increased dietary Met content (from 30% to 45% relative to Lys) accelerated the development of thigh feathers in 16-week-old turkeys (Mróz et al, 2022).…”
mentioning
confidence: 91%
“…The experimental data show that feathers developed rapidly. The lack of an amino acid balance in the diet during this period, especially the balance of sulfur-containing and branched-chain amino acids, can significantly affect early feather development in geese ( Mróz et al, 2022 ). Attention should be paid to the ratios of various amino acids in the feed and the reasonable addition of vitamins and trace elements ( Dersjant and Dusel, 2019 ).…”
Section: Discussionmentioning
confidence: 99%